Quality of fruit juices in terms of physico-chemical, microbiological, thermal and antioxidant properties, evaluation of stability during storage - Dippong, Thomas; Pop, Flavia; Voşgan, Zorica; Mihali, Cristina (Frontiers in Food Science and Technology, 2025)
IntroductionThe storage stability and quality of seabuckthorn, aronia and black currant juices, unsweetened and with added honey, was analyzed in terms of sensory, physico-chemical, microbiological, thermal and antioxidant properties. Methods6 juices assortments were obtained and analyzed using fresh seabuckthorn with honey and without honey, aronia with honey and without honey, black currant with honey and a juice prepared of 50% seabuckthorn and 50% aronia without honey. The thermal analysis of juices which evaluated the thermal behavior of juice assortments in air up to 600 °C. The physico-chemical were analyzed: total sugar content, acidity, dry matter content, electrical conductivity, ascorbic acid content, polyphenol content, pH and antioxidant capacity. Sensory attributes of juices such as appearance, color, smell, taste, foreign bodies were analysed. The microbiological analysis monitored the degree of preservability over time, evaluating the samples immediately after unpacking and subsequently at 7-day intervals up to 56 days of refrigeration.Results and DiscussionThe thermal analysis of juices has been less studied; however, it is highly interesting due to the specifics provided on juice composition and practical uses, particularly the potential to produce dry powder forms of juices. Thermal behavior of juices was assessed. Based on thermal analysis, details on the juice composition were obtained such as dry matter, water content, honey content of juices. The juices showed low pH values (2.78 - 3.75), higher sugar content in the case of honey sweetened juices (38.4 - 42.9 Brix) compared to juices without honey (9.5 - 18.3 Brix), high ascorbic acid content (62.4 - 94.19 mg/100 g), high concentrations of polyphenols (2211.47 - 4614.17 mg EAG/L) and high antioxidant capacity as scavenging capacity of 2,2-diphenyl-1- picrylhydrazyl (DPPH) (87.05 - 94.19 %). The microbiological analysis monitored the degree of preservability over time, evaluating the samples immediately after unpacking and subsequently at 7-day intervals up to 56 days of refrigeration. The microbiological quality of the juices remained within acceptable limits up to the 14th day of refrigeration, after which a significant increase in yeasts and molds was observed, exceeding 5 log CFU/mL. The prepared juices were high in compounds with health benefits such as vitamin C, polyphenols, that showed a high antioxidant capacity and can be consumed up to 14 days of storage in refrigerated conditions.